THE MARRIAGE, DOCUMENTS AND DIVORCE IN TURKEY - Ebuzer Ersoy (UNISSULA, 2021)
Turkish law is applied for all marriage procedures of asylum-seekers, refugees and stateless persons to be conducted in Turkey. Under Turkish law, a Turkish national and an asylum-seeker, refugee or stateless person, or two asylum-seekers or refugees of different nationalities, can be married by the Turkish authorities. All marriages carried out by the Turkish authorities are subject to the Turkish Civil Code and related regulations. Marriages are conducted by marriage officers at the Marriage Departments of municipalities. Couples intending to marry therefore need to submit the relevant documents to municipalities. Please see the section below on the required documents. It is important to note that only official (civil) marriages are legally recognized in Turkey, as defined under the Turkish Civil Code. Other forms of marriage, without an official marriage, are not recognized in Turkey. Getting an official marriage is important as it will secure and guarantee the legal rights of children and of spouses, especially women. Only after the official marriage is a religious marriage (carried out by imams) permitted.